Ramuan Ekor Naga vs. Obat Sintetis : Studi Kontemporer tentang Potensi Analgesik pada Hewan Mencit - Haryanto Haryanto; Alya Nurul Pertiwi; Ummu Aidah; Andi Alisa Alsa; Adinda Maharani; Sumiati Sumiati; Ratri Pramudita; Resti Resti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pain is an unpleasant sensation that can interfere with an individual's quality of life and requires effective management. Synthetic analgesics such as ketorolac, codeine, etoricoxib, and celecoxib are commonly used to relieve pain, but long-term use can cause adverse side effects, including gastrointestinal disturbances, dependence, and cardiovascular risks. Therefore, it is important to find safer, natural alternatives. One promising alternative is the extract of the dragon’s tail leaf (Rhaphidophora pinnata), a plant traditionally used in Indonesian medicine as a pain reliever. This study aims to evaluate and compare the analgesic effects of Rhaphidophora pinnata leaf extract with several synthetic drugs using the writhing test on male mice (Mus musculus). The mice were induced with pain by injecting a 0.5% acetic acid solution. The treatments included ketorolac, codeine, etoricoxib, celecoxib, and Rhaphidophora pinnata leaf extract. The results showed that all treatments, including both synthetic drugs and Rhaphidophora pinnata leaf extract, produced significant analgesic effects compared to the negative control (Na CMC 0.5%). Ketorolac showed the highest effectiveness, followed by codeine, etoricoxib, and celecoxib. Although the Rhaphidophora pinnata leaf extract showed potential as a natural analgesic, its effectiveness varied among individual test animals. Some mice showed a better response to the leaf extract, but overall, the analgesic effect was still lower than that of synthetic drugs. These findings support the use of medicinal plants as a safer alternative to synthetic analgesic drugs. Moreover, this study provides a foundation for further research aimed at isolating active compounds from Rhaphidophora pinnata leaf extract to develop more effective and safer pain-relieving medications.